2018
DOI: 10.1080/15374416.2017.1405354
|View full text |Cite
|
Sign up to set email alerts
|

Distress Tolerance Interacts With Negative Life Events to Predict Depressive Symptoms Across Adolescence

Abstract: Adolescence is a vulnerable period for the development of depressive disorders. Recent research has demonstrated the importance of distress tolerance in the onset and maintenance of depression during adulthood; however, little is known about its role in predicting depressive symptoms among adolescents. The current study examines the effect of distress tolerance and co-occurring negative life events on the developmental trajectory of depressive symptoms from middle to late adolescence. Our sample included 117 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
1
17
0
4
Order By: Relevance
“…DT may be negatively associated with depressive symptoms due to an interaction between DT and stressful events, such that individuals with perceived difficulty tolerating distress engage in maladaptive forms of coping in the face of distress (Felton et al, 2018;Macatee et al, 2016;O'Cleirigh et al, 2007). Distress tolerance may also relate to the ability to tolerate potential positive outcomes, a line of research gaining increased focus in the depression literature, but not yet integrated into theories of distress tolerance (Winer & Salem, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DT may be negatively associated with depressive symptoms due to an interaction between DT and stressful events, such that individuals with perceived difficulty tolerating distress engage in maladaptive forms of coping in the face of distress (Felton et al, 2018;Macatee et al, 2016;O'Cleirigh et al, 2007). Distress tolerance may also relate to the ability to tolerate potential positive outcomes, a line of research gaining increased focus in the depression literature, but not yet integrated into theories of distress tolerance (Winer & Salem, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Though our example includes an individual in the absence of stress, it is unlikely that such an individual exists in the real world, and because of this, one's ability to tolerate distress emerges as an essential component of functioning in day-to-day life. Indeed, an interaction between stressful and/or negative life events and DT on symptoms of depression has been found in both cross-sectional (O'Cleirigh et al, 2007) and longitudinal (Felton et al, 2018;Macatee et al, 2016) studies, indicating that the degree to which stressful and/or negative events leads to symptoms of depression depends on one's ability to tolerate distress. Macatee et al (2016) examined the interaction between DT and stressful events on symptoms of depression while also exploring additional factors.…”
Section: Mechanism Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those with higher DT were more likely to be in the remitting symptom group. Further to this, research has shown that stressful life events throughout adolescence impact those with lower DT more greatly with this group more likely to suffer subsequent depressive symptoms (Felton et al, 2018). It is believed that DT is established in childhood and this may have implication for subsequent mental health trajectories (Felton et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DT has been associated with subsequent youth depressive symptoms, both directly and as moderated by stressful events (Felton et al, 2017(Felton et al, , 2019. Studies have also found that adolescent girls are particularly impaired in maintaining approach behaviors in the face of distress compared to boys (Neumann et al, 2010) and a positive relation between maternal DT and DT in daughters (Daughters et al, 2014).…”
Section: Emotion Regulationmentioning
confidence: 99%